A comparative analysis of development in Southeast European countries - Jednak, Sandra; Kragulj, Dragana; Bulajic, Milica (Technological and Economic Development of Economy, 2018)
There are different kinds of indicators which measure levels of development. The use of varying methods could alter the ranking of a particular country. In this paper, Southeast European countries are ranked according to the World Bank, the UNDP and the I-distance method. The aim of the paper is to provide a comparison between the ranking results obtained with those methods for the period 2007–2012. The principal objective of the study is the ranking of SEE countries using the I-distance technique – a multivariate statistical method for ranking entities – and to discover whether this method gives a better ranking of countries than income per capita and the HDI. To answer this question, similar variables of economic development are used within the research methods. Due to the observed period, some government finance variables are also included. Despite certain limitations, such as lack of data for SEE countries, the results show that the ranks of countries are highly similar regardless of the method used. Nevertheless, there are some differences in the countries’ rankings in some years: there are small differences from year to year both in terms of HDI and GNI per capita. However, the I-distance method shows greater differences between countries.First published online 26 January 2017